Pardon my Frenchie - Rochon, Farrah (Forever, 2024)
"Ashanti Wright is ecstatic over the success of her dog boarding business, Barkingham Palace. In fact, it has become so successful that Ashanti has plans to expand her empire with a doggie bake shop. There's just one problem, the building she's had her eye on has just been sold to the surly grandson of one of her favorite customers. Thaddeus Sims is not a dog person. He's barely a person's person. But when his grandmother is transferred to a senior living facility that doesn't accept pets, the former army officer agrees to care for her annoying Standard Poodle, Puddin'. After all, it was with his grandmother's help that Thad was able to buy the building that will soon house The PX, a sports bar/all-around hangout space for former servicemen that he plans to open. Puddin' and Ashanti's French Bulldog, Duchess, have become a bit of a sensation on Barkingham Palace's livestream because of their budding romance. When a video of the dogs sharing a doggy treat Lady and the Tramp-style goes viral, their owners are sucked into a media frenzy that captures the nation by storm...and creates some sparks for their owners too"--